School absenteeism among orphans and vulnerable children in Lagos State, Nigeria: a situational analysis (2017)
Knowledge of factors associated with school absenteeism among orphans and vulnerable children (OVC) who are at greater risk could facilitate effective policies to mitigate school dropouts. This study assessed the level of school absenteeism and its associated factors among OVC in five local government areas (LGAs) in Lagos State, Nigeria. A cross-sectional study of OVC households in purposively selected five LGAs in Lagos State was conducted. Enrolled vulnerable households were based on the National Household Vulnerability Assessment criteria. School absenteeism was measured by whether the OVC missed any school day, for any reason in the last school week. Data were collected by personal interview using a semi-structured questionnaire. IBM SPSS Statistics, version 20, was used for all analysis of data collected on schooling of OVC aged 10–17 years. Chi-square test and logistic regression model were used to determine significance of associations at 5% level. The 757 OVC participants were aged 13.1±2.2 years and their caregivers were aged 43.1 ±13.9 years from 1300 households. There was high proportion of school enrolment (85.7%) as well as absenteeism (20%). The rate of absenteeism among OVC was significantly higher among those who involved in household chores (31.2%) and who often sleep at night without food (40.0%). The odds of absenteeism were almost twice higher among OVC who involved in household chores (odds ratio [OR]: 1.93, 95% confidence interval [CI]: 1.14– 3.27), whose guardian could not pay unexpected expenses (OR: 1.78, 95% CI: 1.05–3.02) and those from households where there was often no food (OR: 1.84, 95% CI: 1.04–3.27). A high rate of OVC school enrolment might not translate to regular school attendance. Also, a high proportion of school absenteeism can be attributed to OVC engagement in house chores, poor economy and food insecurity. Economic empowerment of OVC care givers may improve school attendance.